Tax Policy of the Fourth Estate? On the Perspectives and Limits of the Political Cooperation of the Moravian Territorial Lord’s Towns before the Battle at White Mountain - Sterneck, Tomáš (Historical Studies on Central Europe, 2021)
The study deals with questions of the political cooperation of Moravian territorial lord’s towns (the Moravian Fourth Estate) in the sixteenth and early seventeenth century. This issue is viewed through the prism of political negotiations about the very high tax burden on the towns. After an outline of the structure of the estate-organized society of the Moravian Margraviate and the role of territorial lord’s—royal and chamber—towns in it, the article introduces the natural and fiscal burdens weighing down the urban organisms and escalating in line with the wars of the Habsburg Monarchy against the expansive Ottoman Empire. The burden on Moravian towns was much heavier than on other segments of the estate-structured society. This was the basis for the towns’ concerted efforts to find relief, which manifested itself during the Fifteen Years’ War with the High Porte in 1593–1606. Surviving sources offer detailed documentation of the 1604 negotiations, when at the initiative of Brno, an attempt was made to counter the pressure of the higher estates that intended to further increase the tax burden on territorial lord’s towns. However, these negotiations illustrate that effective joint action of the town representations was hindered by individual municipalities’ particular interests. Individualism generally exacerbated the towns’ weak position in the political system of the time. In the broader coordinates of early modern Europe, in the Bohemian lands, urban space was less developed and the bourgeoisie was significantly weaker than in their Western and Southern European counterparts. Therefore, the limited coordination of the territorial lord’s towns in the fight against the higher estates did not lead to the desired results.